Disempowering Mindfulness: Reflections on Discovering the Veils of Power in Well-Being and Good Intentions (LEARNing Landscapes, 2017)
Despite the widespread popularity of mindfulness as a wellness intervention strategy across educational levels, its proponents are susceptible to countering the intended area of improvement. This article recounts the cumulative reflections of an educator and his attempts to implement mindfulness into high school classes at the Los Angeles County Jail. Beginning with a layout of the physical and social settings, the article examines the ways that unconsciously practicing mindfulness will counter and potentially negate the possible benefits of mindful practice.
Keywords: mindfulness; high school; well-being